2018
DOI: 10.1200/jgo.18.61900
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Telemedicine Platform for Radiation Oncology Training and Peer Review

Abstract: Background: Telemedicine has been posited as a potential means of bolstering radiation therapy delivery in developing nations. World Aid Exchange (WaidX) is an innovative intercontinental telemedicine platform oriented to oncology specialties. This platform, devoted to reducing the digital divide on health practice, provides telecommunication services between health care facilities in developed and developing countries. It conveys the ability to safely share radiologic images and patient medical records for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Australia and internationally, peer review has been reported to improve patient care both directly and indirectly and be feasible within radiation oncology facilities 6–35 . The American Society for Radiation Oncology (ASTRO) surveyed members in 2013 to establish peer review practice patterns, 36 with the majority of the 572 participating physicians supporting formal recommendation and guidance on peer review.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and internationally, peer review has been reported to improve patient care both directly and indirectly and be feasible within radiation oncology facilities 6–35 . The American Society for Radiation Oncology (ASTRO) surveyed members in 2013 to establish peer review practice patterns, 36 with the majority of the 572 participating physicians supporting formal recommendation and guidance on peer review.…”
Section: Introductionmentioning
confidence: 99%